Words in a Cultural Context - Kavanagh, Kathryn (Lexikos, 2000)
Abstract: Successful communication is dependent upon an adequate level of cultural as well as linguistic understanding. Language is itself part of culture and reflects social structures and attitudes. lbis paper examines the case for dictionaries to carry cultural as well as lexical information. It reviews the American tradition and purpose of including cultural material in dictionaries, and considers the nature and scope of cultural information contained in a number of modem American and European dictionaries. Various means of presenting cultural information are also examined. The paper concludes by considering the implications for lexicographers developing dictionaries in multicultural South Africa. Keywords: COMMUNICATION, CROSS-CULTURAL COMMUNICATION, CULTURAL INFORMATION, CULTURE, CURRICULUM, DICTIONARIES FOR SPECIAL PURPOSES, DICTIONARY, DICTIONARY DESIGN, ENCYCLOPEDIA, ENCYCLOPEDIC DICTIONARIES, LANGUAGE, LEXICOGRAPHY, MULTICULTURAL SOCIETY, SOUTH AFRICA Opsomming: W oorde binne In kulturele konteks. Suksesvolle kommunikasie berusop ’n voldoende vlak van kulturele sowel as taalkundige begrip. Taal self is deeJ van kuJtuur enweerspieiH sosiale strukture en houdings. Hierdie artikel ondersoek die insluiting van sowel kultureleas leksikale inIigting in woordeboeke. Dit beoordeel die Amerikaanse tradisie en doel daarmeeom kulturele materiaal in woordeboeke in te sluit, en oorweeg die aard en omvang van kultureleinIigting vervat in ’n aantal moderne Amerikaanse en Europese woordeboeke. Verskillendemaniere om kulturele inIigting aan te bied, word ook ondersoek. Die artikel sluit af deur die implikasiesvir leksikograwe te oorweeg wat woordeboeke saamstel in multikulturele Suid-Afrika. Sleutelwoorde: KOMMUNIKASIE, INTERKULTURELE KOMMUNIKASIE, KULTURELEINLIGTlNG, KULTUUR, KURRIKULUM, WOORDEBOEKE MET SPESIALE OOGMERKE,WOORDEBOEK, WOORDEBOEKONTWERP, ENSIKLOPEDIE, ENSIKLOPEDIESE WOORDEBOEKE,TAAL, LEKSIKOGRAFIE, MULTIKULTURELE SAMELEWING, SUID-AFRIKA